CMR imaging biosignature of cardiac involvement due to cancer-related treatment by T1 and T2 mapping. (15th January 2019) - Haslbauer, Jasmin D.; Lindner, Sarah; Valbuena-Lopez, Silvia; Zainal, Hafisyatul; Zhou, Hui; D'Angelo, Tommaso; Pathan, Faraz; Arendt, Christophe A.; Bug, Gesine; Serve, Hubert; Vogl, Thomas J.; Zeiher, Andreas M.; et al.
Abstract: Background: Cancer-related treatment is associated with development of heart failure and poor outcome in cancer-survivors. T1 and T2 mapping by cardiovascular magnetic resonance (CMR) may detect myocardial injury due to cancer-related treatment. Methods: Patients receiving cancer-related treatment regimes underwent screening of cardiac involvement with CMR, either within 3 months (early Tx) or >12 months (late Tx) post-treatment. T1 and T2 mapping, cardiac function, strain, ischaemia-testing, scar-imaging and serological cardiac biomarkers were obtained. Results: Compared to age/gender matched controls (n = 57), patients (n = 115, age (yrs): median(IQR) 48(28-60), females, n = 60(52%) had reduced left ventricular ejection fraction (LV-EF) and strain, and higher native T1 and T2. The early Tx group (n = 52) had significantly higher native T1, T2 and troponin levels compared to the late Tx group, indicating myocardial inflammation and oedema (p < 0.01). On the contrary, late Tx patients showed raised native T1, increased LV-end-systolic volumes, reduced LV-EF and deformation, and elevated NT-proBNP, suggesting myocardial fibrosis and remodelling (p < 0.05). Prospective validation of these results in an independent cohort of patients with similar treatment regimens (n = 25) and longitudinal assessments revealed high concordance of CMR imaging signatures of early and late cardiac involvement. Conclusions: Native T1 and T2 mapping can be valuable in detecting and monitoring of cardiac involvement with cancer-related treatment, providing distinct biosignatures of early inflammatory involvement (raised native T1 and T2) and interstitial fibrosis and remodelling (raised native T1 but not T2), respectively. Our findings may provide an algorithm allowing to identify susceptible myocardium to potentially guide cardio-protective treatment measures. Highlights: We provide for novel and important insight into the pathophysiological changes and dynamics of myocardial injury in the presence of cancer-related treatments. Using CMR tissue imaging markers T1 and T2 mapping we reveal distinct biosignatures of early and late myocardial involvement due to cancer-related treatment. Early inflammatory involvement is signified by raised native T1 and T2. Late myocardial involvement by interstitial fibrosis and remodelling is outlined by raised native T1 but not T2. This imaging signature provides an algorithm to identify susceptible myocardium and guide cardio-protective treatment measures, supporting personalised care of patients with susceptible myocardium.